Damage mechanism and fatigue strength prediction of compacted graphite iron with different microstructures. (November 2022) - Chen, Y.; Pang, J.C.; Li, S.X.; Zou, C.L.; Zhang, Z.F.
Highlights: Compacted graphite iron with high pearlite content has higher strengths. Debonding at the graphite/ferrite interface causes fatigue crack initiation. A model for predicting the fatigue strength of compacted graphite iron was proposed. Abstract: The effects of microstructures on the tensile properties, high-cycle fatigue properties and corresponding damage mechanism of compacted graphite iron (CGI) were investigated. The results show that with the increase of pearlite content, both the tensile strength and fatigue strength show an upward trend. Fatigue cracks usually initiate at the graphite/ferrite interface and gradually propagate into the matrix under the high-frequency cyclic stress. The adjacent cracks bridge to form the main crack, leading to the final fracture. Based on the pearlite content and tensile strength, a new model for predicting the fatigue strength of CGI with high accuracy was proposed.